EFFECTIVENESS OF VILLAGE FUND USE IN INFRASTRUCTURE DEVELOPMENT IN RANDEGAN VILLAGE, TANGGULANGIN DISTRICT, SIDOARJO REGENCY - Aulia, Firda Divanda; Sukmana, Hendra (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to assess the effectiveness of Village Fund utilization in infrastructure development in Randegan Village, Tanggulangin District, Sidoarjo Regency, during the 2022-2024 fiscal year. The study focuses on the alignment of the program’s planning, implementation, and evaluation processes with community needs and established village development priorities. Method: This research was conducted using a descriptive approach, collecting data through interviews with village officials and community members, as well as reviewing village budget (APBDes) reports. The analysis process was based on the effectiveness theory proposed by Sutrisno (2007), using five main indicators as benchmarks. Through these indicators, the effectiveness of Village Fund management can be comprehensively assessed, including in terms of planning, implementation, and community outcomes. Results: Based on the research results analyzed using Sutrisno’s (2007) theory of effectiveness with its five elements, several important findings can be obtained. First, in the aspect of Program Understanding, the village government, community, and village institutions have a good understanding of the mechanisms, objectives, and direction of development, where the deliberation process takes place effectively. Second, in the aspect of Right on Target, the infrastructure development program has been in accorcance with the needs of the local community. Third, in terms of Timeliness, most of the development was carried out on schedule through the self-management system, although there were external obstacles in the form of delays in the disbursement of funds. Fourth, in terms of Achivement of Goals, the realized development provided real benefits such as ease of access to infrastructure, increased productivity in the agricultural sector, and eonomic empowerment of local communities. Fifth, in the aspect of Real Change, there were significant changes in both physical and socio-economic forms that were directly felt by village residents. Novelty: The application of the five-indicator effectiveness model in the context of village infrastructure development, which combines policy analysis with field facts, and in this study it was found that self-management is not only cost-efficient, but also has an impact on local community empowerment.